Estimation of the level of some heavy metals in the treated wastewater returned to the Diyala River from the Rustamiya plant in Baghdad (Journal of the College of Basic Education, 2023)
The current study aims to detect the level of heavy elements (lead, cadmium, manganese, copper, iron and zinc) in five successive sites of the wastewater treatment plant of the Rustamiya project, south of Baghdad, by taking weekly samples during the month of March of 2011 from the source of untreated water and primary aeration ponds. Pre-Aeration, Prim-settling, Final Treatment, and Post-chlorination, the symbols (Cl2, F, PS, PA, C) were given, respectively. Sludge samples drawn from sewage sediments were also taken for the same purpose.The results showed that there were significant concentrations of all the studied elements at levels close to their values in the untreated wastewater, where their levels were in (C)Crude water (0.302,4.947, 0.094, 0.285,0.005,0.007 mg/L) and in the sterilized water from the station after chlorination (Cl2). ) (0.727, 2.312, 0.101, 0.327, 0.0036, 0.0056 mg/L), respectively, and chemical analyzes showed the presence of the same elements in sludge components at concentrations (0.044, 2.74, 0.041, 0.022, 0.0001, 0.016 mg/L). When following up the flow of treated and expelled water to the Diyala River, all the previous elements were also recorded in concentrations (0.001, 0.18, 0.021, 0.083, 0.0005, 0.025) μg / kg dry weight. Which shows that the treatment process was not able to remove the heavy elements, and it needs to add advanced treatment stages, as is the practice in modern stations in the countries of the world. The study also points out the need to conduct studies on farms that use this sludge in the fertilization process in the agricultural areas around Baghdad and its suburbs.